A Cinematographic Contemplation on Rūmi's Assertion - What You Seek, Is Seeking You - Mohammad Yari, Reza (Auckland University of Technology, 2024)
The concept of identity has been discussed for many centuries in Persian literature, distinctively in the poems of the philosopher and poet Rūmi (Jalal al-Din Muhammad Balkhi - (جلال‌الدین محمد بلخی‎) (1207 –1273). Identity and Rūmi’s poetic thinking form the substrate from which this study emanates. Methodologically the research employs a heuristic, practice-led, inquiry, to consider the poetics of سیر (Seyr) and سلوک (Soluk) through the four Zoroastrian sacred elements آب، باد، خاک، و آتش (fire, earth, water and air movement). In the resulting two non-verbal films, the lyrical potentials of cameras, lenses and composition are employed to create subtle cultural allusions that function as poetic metaphors. Using this approach the work contributes to a corpus of work by Persian filmmakers who employ poetic abstraction as a means of enhancing philosophical contemplation.